Skills Development for Sustainable Manufacturing - Olakitan Ijagbemi, Christianah; Moody Campbell, Harold (IntechOpen, 2017)
Globally, manufacturing facilities have taken a new turn with a mix of advanced robotics to fully unify production systems. Today's era of manufacturing has embraced smart manufacturing techniques by delving into intelligent manufacturing system of advances in robotics, controllers, sensors, and machine learning giving room for every aspect of the plant to be constantly accessible, monitored, controlled, redesigned, and adapted for required adjustments. Skill development within the manufacturing sector presents the advantage of high-quality products and can as well address long-term employment concerns through job creation. The development of skills for sustainable manufacturing is crucial to ensuring an efficient transition to a competitive economy by matching supply and demand for key skills. A number of factors ranging from green innovation, climate change, advances in technology, and global economic downturn are driving the need for a competitive and sustainable manufacturing value chain. The complexity of today's factories calls for new and existing workers to up-skill in order to influence design changes and production efficiency toward sustainable manufacturing.